Investigating the Factors Affecting Purchase Intention of Muslim Women Towards Halal Cosmetics - Kamalul Ariffin, Shaizatulaqma; Fadhilah Azra, Wihdatul; Abdul Wahid, Nabsiah; Yen Nee, Goh (Journal of Entrepreneurship, Business and Economics; Vol 7 No 2s (2019): Special Issue: Contemporary Business Issues in Malaysia: How does this “Tiger Cub” feel today?, 2019)
The objective of this study is to examine the relationship between brand awareness, attitude, subjective norms, perceived behavioural control and purchase intention towards halal cosmetics among Muslim women in Indonesia. The questionnaires were distributed to 304 Muslim women at Medan, Banda Aceh, and DKI Jakarta within end of January until early February 2019. To investigate the relationships between factors; the structural equation modelling (SEM-PLS) version 2.0 was used to analysed the data. The finding of this study has found that two components of TPB (attitude, perceived behavioural control) and brand awareness are positively related with purchase intention towards halal cosmetics, while subjective norm is found to be insignificant. The result shows that positive attitude is the most important factor to increase consumer purchase intention toward halal cosmetics. The result of this study provides information to cosmetics’ firm that Muslim women with high brand awareness, attitude and perceived behavioral control will have high purchase intention toward halal cosmetic products. The findings of this study contribute valuable information to scholars, policy makers and firms in order to understand Muslim customers in Indonesia. Research paper  Keywords: Corporate Governance, Firm Values, Firm Size, Gender, Tobin Q, Board Reference to this paper should be made as follows: Kamalul Ariffin, S., Fadhilah Azra, W., Abdul Wahid, N., & Yen Nee, G. (2019). Investigating the Factors Affecting Purchase Intention of Muslim Women Towards Halal Cosmetics, Journal of Entrepreneurship, Business and Economics , 7 (2s), 78–105.